Developmental Plasticity in Butterfly Eyespot Mutants: Variation in Thermal Reaction Norms across Genotypes and Pigmentation Traits - Mateus, Ana Rita Amaro (2022)
Developmental plasticity refers to the property by which a genotype corresponds to distinct phenotypes depending on the environmental conditions experienced during development. This dependence of phenotype expression on environment is graphically represented by reaction norms, which can differ between traits and between genotypes. Even though genetic variation for reaction norms provides the basis for the evolution of plasticity, we know little about the genes that contribute to that variation. This includes understanding to what extent those are the same genes that contribute to inter-individual variation in a fixed environment. Here, we quantified thermal plasticity in butterfly lines that differ in pigmentation phenotype to test the hypothesis that alleles affecting pigmentation also affect plasticity therein. We characterized thermal reaction norms for eyespot color rings of distinct Bicyclus anynana genetic backgrounds, corresponding to allelic variants affecting eyespot size and color composition. Our results reveal genetic variation for the slope and curvature of reaction norms, with differences between eyespots and between eyespot color rings, as well as between sexes. Our report of prevalent temperature-dependent and compartment-specific allelic effects underscores the complexity of genotype-by-environment interactions and their consequence for the evolution of developmental plasticity.